1984
DOI: 10.1007/bf00427447
|View full text |Cite
|
Sign up to set email alerts
|

Attention, memory, and cigarette smoking

Abstract: Four experiments tested the effects of smoking one cigarette on verbal memory and attention. In Experiment I, 18 men were tested under three conditions in a repeated-measures design (pretrial smoking, posttrial smoking, no smoking). Recall of a 50-word list was tested immediately and after intervals of 10 and 45 min. Pretrial smoking resulted in improved recall 10 and 45 min after learning, but not immediately. Posttrial smoking was ineffectual. In Experiment II, three posttrial smoking intervals (1, 5, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…This possible methodological artifact might be explored in future work to determine whether the CO 2 -enriched air paradigm is indeed useful in the comparison of smoking versus cigarette deprivation in anxious responsivity. Lastly, since nicotine administration has been shown to have acute attentionamplifying effects as a stimulant drug (Peeke & Peeke, 1984;Rusted & Warburton, 1992), it is possible that the smoking-asusual group was more attuned to their anxiety and to the laboratory challenge paradigm amplifying anxiety levels overall.…”
Section: Discussionmentioning
confidence: 99%
“…This possible methodological artifact might be explored in future work to determine whether the CO 2 -enriched air paradigm is indeed useful in the comparison of smoking versus cigarette deprivation in anxious responsivity. Lastly, since nicotine administration has been shown to have acute attentionamplifying effects as a stimulant drug (Peeke & Peeke, 1984;Rusted & Warburton, 1992), it is possible that the smoking-asusual group was more attuned to their anxiety and to the laboratory challenge paradigm amplifying anxiety levels overall.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have reported acute, nicotine-induced facilitation of cognitive function in humans (Andersson and Post 1974;Houston et al 1978;Peeke and Peeke 1984;Warburton etal. 1986;West and Hack 1991).…”
Section: Acute Effectsmentioning
confidence: 98%
“…In addition to its rewarding effects, acute nicotine has cognitive enhancing properties in humans. Specifically, acute nicotine administration enhances attention (Parrott and Craig 1992;Bates et al 1995;Hahn et al 2007;Hong et al 2011), learning and memory (Mangan and Golding 1983;Peeke and Peeke 1984;Warburton et al 1986;Colrain et al 1992), and information processing (Wesnes and Warburton 1983;Provost and Woodward 1991;for review, see Sherwood 1993). In agreement with human studies, there is a great body of evidence suggesting that acute nicotine augments hippocampus-dependent contextual and spatial learning and memory while not affecting hippocampus-independent subtypes of learning (e.g., cued learning) in rodents.…”
Section: Nicotinementioning
confidence: 99%